The oncolytic peptide LTX-315 kills cancer cells through Bax/Bak-regulated mitochondrial membrane permeabilization - Zhou, Heng (Oncotarget, 2015)
LTX-315 has been developed as an amphipathic cationic peptide that kills cancer cells. Here, we investigated the putative involvement of mitochondria in the cytotoxic action of LTX-315. Subcellular fractionation of LTX-315-treated cells, followed by mass spectrometric quantification, revealed that the agent was enriched in mitochondria. LTX-315 caused an immediate arrest of mitochondrial respiration without any major uncoupling effect. Accordingly, LTX-315 disrupted the mitochondrial network, dissipated the mitochondrial inner transmembrane potential, and caused the release of mitochondrial intermembrane proteins into the cytosol. LTX-315 was relatively inefficient in stimulating mitophagy. Cells lacking the two pro-apoptotic multidomain proteins from the BCL-2 family, BAX and BAK, were less susceptible to LTX-315-mediated killing. Moreover, cells engineered to lose their mitochondria (by transfection with Parkin combined with treatment with a protonophore causing mitophagy) were relatively resistant against LTX-315, underscoring the importance of this organelle for LTX-315-mediated cytotoxicity. Altogether, these results support the notion that LTX-315 kills cancer cells by virtue of its capacity to permeabilize mitochondrial membranes.